2018
DOI: 10.2174/1871526518666180416110259
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Drug Resistance Profiles for the HIV Protease and Reverse Transcriptase Gene in Patients Receiving Combination Therapy in Tehran, Iran

Abstract: An antiretroviral treatment consisting of nucleoside reverse transcriptase inhibitor, non-nucleoside reverse transcriptase inhibitor and protease inhibitor, impairs the emergence of a resistant strain and descends its prevalence among the community. Having a high rate mutation in participants of this study raises concerns about treatment failure in HIV infected people in Iran. Observing high mutations rates in participants of this study raises concerns about treatment failure in HIV infected people in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies from MENA, most of which are from Iran, are largely composed of quantitative surveys, producing lists of risk and protective factors for treatment adherence. [7][8][9][10][11][12][13][14] Our findings suggest that the three key affective and cognitive mechanisms of denial, fear and despair undermine successful and lifelong treatment. We detail the ways in which denial and fear are triggered through a context of negative societal perceptions, lack of awareness regarding HIV and widespread misinformation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies from MENA, most of which are from Iran, are largely composed of quantitative surveys, producing lists of risk and protective factors for treatment adherence. [7][8][9][10][11][12][13][14] Our findings suggest that the three key affective and cognitive mechanisms of denial, fear and despair undermine successful and lifelong treatment. We detail the ways in which denial and fear are triggered through a context of negative societal perceptions, lack of awareness regarding HIV and widespread misinformation.…”
Section: Discussionmentioning
confidence: 90%
“…Protected by copyright. BMJ Global Health few studies conducted within MENA, most focus on prevalence or biomedical aspects of the condition, [7][8][9][10] and studies of adherence focus on identifying key affected populations, such as people who use drugs and imprisoned individuals at risk of non-adherence. 11 12 Quantitative and biomedical studies promote understanding about the prevalence and risk profiles of non-adherence among key affected groups, 13 14 and can increase knowledge on drug resistance profiles to antiretroviral therapy in different settings.…”
Section: Key Questionsmentioning
confidence: 99%
“…These findings are consistent with previous studies demonstrating the high prevalence of drug resistance mutations among HIV-1-positive patients in Iran (25,26). For instance, Sadeghi et al conducted a study where they found that out of 17 patients, 2 (12%) had major PI resistance mutations, while 7 (41%) had minor PI resistance mutations (27). Another study conducted in Iran showed that 32% of patients undergoing antiretroviral treatment had mutations related to PI drug resistance (28).…”
Section: Discussionmentioning
confidence: 99%